2020
DOI: 10.1136/bmjopen-2020-039639
|View full text |Cite
|
Sign up to set email alerts
|

Protocol of a prospective, multicentre phase I study to evaluate the safety, tolerability and preliminary efficacy of the bispecific PSMAxCD3 antibody CC-1 in patients with castration-resistant prostate carcinoma

Abstract: IntroductionProstate cancer is the second most common cancer in men worldwide. When the disease becomes resistant to androgen-deprivation therapy, treatment options are sparse. To address the high medical need in castration-resistant prostate cancer (CRPC), we generated a novel PSMAxCD3 bispecific antibody termed CC-1. CC-1 binds to prostate-specific membrane antigen that is expressed on prostate cancer cells and tumour vessels, thereby allowing a dual anticancer effect.Methods and analysisThis first in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In summary, our findings encourage the implementation of MS technology to analyze impurities and the integrity of recombinant antibodies. This allowed in our case to meet GMP regulations and to initiate a clinical trial with CC-1 (Heitmann et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In summary, our findings encourage the implementation of MS technology to analyze impurities and the integrity of recombinant antibodies. This allowed in our case to meet GMP regulations and to initiate a clinical trial with CC-1 (Heitmann et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…In summary, our findings encourage the implementation of MS technology to analyze impurities and the integrity of recombinant antibodies. This allowed in our case to meet GMP regulations and to initiate a clinical trial with CC-1(Heitmann et al, 2020).ACKNOWLEDGMENTSWork of the authors is supported by funds of the Bundesministerium für Bildung und Forschung (BMBF) and the Ministry of Economy of Baden-Württemberg in the framework of the Excellence Strategy of the University of Tübingen. In addition, this study was supported by the German Cancer Consortium and the Helmholtz validation fund (OPTIMAB).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Accordingly, in the last decade, several studies reported on this and other PSMA targeting radiolabeled agents that showed clinical activity in CRPC [ 57 , 58 , 59 , 60 ]. In line, a plethora of preclinically characterized therapeutic constructs and almost all bsAbs that underwent clinical evaluation in PC are directed to PSMA [ 61 , 62 , 63 , 64 ].…”
Section: Bsabs In Prostate Cancermentioning
confidence: 99%
“…In line with the first notion, pharmacokinetic studies in mice showed the expected long serum half-life as compared to smaller formats missing an Fc part. An open-label, multicenter dose escalation and dose expansion phase I trial is effectively recruiting since 2019 (patients with CRPC) [ 62 ], with highly promising clinical results regarding lacking immunogenicity (development of ADAs), safety, and also efficacy.…”
Section: Current Bsabs Under Clinical Evaluationmentioning
confidence: 99%